ESTIMATION OF RICE SEED PRODUCTION EFFICIENCY USING THE STOCHASTIC FRONTIER PRODUCTION FUNCTION - Adri, Adri; Firdaus, Firdaus; Suharyon, Suharyon; BS, Busra; Yarda, Yarda; Hendayana, Rachmat; Edi, Syafri (LPPM Universitas Jambi, 2023)
Production efficiency is a crucial factor in producing seeds. This paper aims to estimate the level of efficiency of rice seed production and determine the factors that influence it using a frontier stochastic production function approach. The rice varieties developed are Inpara3, Inpari Nutri Zink and Baroma. The research was conducted in Rawa Medang Village, Batang Asam District, West Tanjung Jabung Regency, Jambi Province, in December 2021. Data collection was carried out through observation and in-depth interviews with seed breeders. By using the frontier production function, the conclusion is obtained: The efficiency level of rice farming for superior varieties is relatively good, with the efficiency level at level 6. All rice seed breeders show effective performance. To increase the efficiency of rice farming in the future, it is necessary to sharpen the use of production input inputs. The consideration is that the breeder's orientation is to produce quality seed for use by the farming community. Therefore, more intensive technological assistance is needed.